MATH 115: Lecture VII Notes
MATH 115: Lecture VII Notes
) Computing the instantaneous rate of change of the unit price when x = 5000 tires
boils down to a problem of evaluating the difference quotient as h approaches 0. We have that
D(x + h) − D(x)
D� (x) = lim = lim (−2x − h) = −2x.
h→0 h h→0
We conclude that the instantaneous rate of change for the unit price of tires when exactly 5000
tires are demanded is D� (5) = −$10. �
from which it follows that lim f (x) = f (a). We conclude that f is continuous at x = a.
x→a
3 Differentiation
3.1 Basic Rules of Differentiation
3.1.1 Four Basic Rules
Recall that in the prequel, our method for computing derivatives of functions was to tediously
hash out the definition of the derivative as a limit of a difference quotient. Our goal in this chap-
ter is to provide rules of differentiation that expedite the process. We note that all of these rules
can be established by using the limit definition of the derivative. Given a differentiable func-
d
tion f (x), i.e., any function whose derivative exists, we will use the notation dx f (x) to denote
the derivative of f (x) with respect to the variable x. Often, it is more convenient to simply write
f � (x) for the derivative of f (x) with respect to x when the variable of differentiation x is clear.
Derivative of a Constant. The derivative of a constant function is equal to zero. Explicitly,
d
given a constant function f (x) = C for some real number C, we have that dx f (x) = 0.
Proof. Using the limit definition of the derivative, we have that
d f (x + h) − f (x) C −C
f (x) = lim = lim = lim 0 = 0.
dx h→0 h h→0 h h→0
24
Compute the derivatives of the following constant functions.
(a.) f (x) = 27
(b.) g(x) = e2
(c.) h(x) = √1
2π
d n
Derivative of a Power Function. Let n be any real number. We have that dx
x = nxn−1 .
Proof. Consider the case when n is a positive integer. Using the limit definition of the derivative
and the Binomial Theorem, we have that
d n (x + h)n − xn
x = lim
dx h→0 h
�n � �n � � n
�
xn + 1
xn−1 h + 2
xn−2 h2 + · · · + n−1
xhn−1 + hn − xn
= lim
h→0 h
��n� �n � � n
� �
h 1
xn−1 + 2
xn−2 h + · · · + n−1
xhn−2 + hn−1
= lim
h→0 h
�� � � � � � � � �
n n−1 n n−2 n n−2 n−1 n n−1
= lim x + x h + ··· + xh +h = x = nxn−1 .
h→0 1 2 n−1 1
We note that our proof establishes the case where n is a positive integer; however, our theorem
claims that the result holds for all real numbers. We will return to prove this fact after we have
visited the topic of implicit differentiation. Compute the derivatives of the following functions.
(a.) f (x) = x6
(d.) p(x) = xe
Proof. Consider the function g(x) = C · f (x). We will assume that f � (x) exists. Using the limit
definition of the derivative, we have that
g(x + h) − g(x) C · f (x + h) − C · f (x) f (x + h) − f (x)
g � (x) = lim = lim = C · lim = C · f � (x).
h→0 h h→0 h h→0 h
d d
Using our alternative notation, we conclude that dx
[C · f (x)] = C · dx
f (x).
Compute the derivatives of the following functions.
(a.) f (x) = 5x3
25
(b.) g(x) = √3
x
Proof. Like usual, we will defer to the limit definition of the derivative. Because it is not very
enlightening, we leave the proof as an exercise for the reader.
Compute the derivatives of the following functions.
Recall that the derivative of a function f (x) at a point (x, f (x)) gives the equation of the slope
of the line tangent to f (x) at the point (x, f (x)). For instance, we have seen that the slope of the
line tangent to f (x) = 7x + 1 is f � (x) = 7 for every real number x. We have justified this fact both
heuristically and with calculus. We now extend this notion to a more complicated function.
Equation of the Tangent Line. Compute the slope of the line tangent to the function f (x) =
2x + √1x at the point (1, 3). Use this slope to find the equation of the tangent line at (1, 3).
We note that f � (x) gives the slope of the line tangent to f (x) at any point (x, f (x)). We are con-
cerned with the point (1, 3), in particular, hence we wish to find the slope of the line tangent to
f (x) when x = 1. We have that f � (1) = 2 − 12 = 32 . Our problem is now reduced to a question of
algebra. Using the point-slope form y − y1 = m(x − x1 ) with (x1 , y1 ) = (1, 3) and m = 32 , we find
that the equation of the tangent line at (1, 3) is given by y − 3 = 32 (x − 1). Cleaning this up a bit,
we find that y = 32 x + 32 . Graphing both of these equations should corroborate our result. �
Proof. We omit the proof here on the grounds that it is tricky and tedious, but we note that Tan
provides an excellent exposition on pages 176 and 177 in the textbook.
26